Managing content marketing : The real-world guide for creating passionate subscribers to your brand - Rose, Robert (Marketing executive) (Cleveland, Ohio, CMI Books, 2011)
Let's face it...content marketing is all the rage. Brands around the world are spending (on average) over 25% of their total marketing budget on content marketing. What's been missing...until now...is the book that tells marketers exactly how to put content marketing to work. Managing Content Marketing shows you, in detail, how to manage content marketing within your organization. Whether you come from a small company or multi-billion dollar brand, this book gives you the ammunition and the ideas to develop a storytelling process that will create passionate subscribers to your brand. World-renowned content marketing experts Robert Rose and Joe Pulizzi have teamed up to help marketing pros and business owners develop a content marketing plan that goes beyond theories and explains exactly how to turn that plan into reality. Managing Content Marketing will teach you to: --Build the Business Case for Content Marketing --Develop a Content Marketing Strategy that Works for Your Business --Tell a Consistent Story that Engages Your Customers --Determine the Right Marketing Channels to Implement --Create an Internal and External Workflow for Content Marketing --Measure Content Marketing and Communicate Results to Internal Stakeholders